On solving the minimization problem and the fixed-point problem for nonexpansive mappings in CAT(0) spaces. (2nd January 2017) - Suparatulatorn, Raweerote; Cholamjiak, Prasit; Suantai, Suthep
Abstract : We propose a new modified proximal point algorithm combined with Halpern's iteration process for nonexpansive mappings in the framework of CAT(0) spaces. We establish a strong convergence theorem under some mild conditions. Our results extend some known results which appeared in the literature.